Efficacy and Tolerability of Switching to Ziprasidone in Italian Patients with Acute Exacerbation of Schizophrenia: An Open-Label Trial - Mencacci, C.; null (Pharmacopsychiatry, 2012)
The long-term maintenance of a stable condition is an important aim of schizophrenia therapy, which frequently requires the switch between 2 antipsychotic agents. This 8-week multicenter study, conducted in Italy, evaluates the switch from a previous antipsychotic to ziprasidone.Adult acute schizophrenic patients requiring a change in antipsychotic for lack of efficacy or tolerability issues took ziprasidone 20 − 80 mg/bid. Dosages could be adjusted during the study. The primary efficacy outcomes were the differences in positive and negative syndrome scale (PANSS) and clinical global impression severity (CGI-S) scores from baseline to study end. Other efficacy variables were clinical global impression improvement, global assessment of functioning, patient preference scale and drug attitude inventory.189 patients were evaluated; the mean (±SD) ziprasidone dose was 95.9±34.5 mg/day. PANSS and CGI-S scores significantly decreased throughout the study. All secondary outcomes significantly improved at the end of the study vs. baseline values. Ziprasidone was well tolerated; 13 patients reported a QTc prolongation (mild in 12 patients).Notwithstanding the limitations of any non-comparative study, these results suggest that ziprasidone may be an effective and well-tolerated option in acute schizophrenia patients who discontinued a previous antipsychotic agent.
Keywords: acute exacerbation; antipsychotic agents; schizophrenia; switch; ziprasidone